2001
DOI: 10.1016/s0925-4773(00)00512-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of endoreduplication domains in the Drosophila gut by the knirps and knirps-related genes

Abstract: Endoreduplication cycles that lead to an increase of DNA ploidy and cell size occur in distinct spatial and temporal patterns during Drosophila development. Only little is known about the regulation of these modified cell cycles. We have investigated fore- and hindgut development and we present evidence that the Drosophila knirps and knirps-related genes are key components to spatially restrict endoreduplication domains. Our lack and gain-of-function experiments show that knirps and knirps-related which encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…We found that both vvl-RNAi and kni-RNAi larvae have mildly reduced PG nuclei and cell size, which is likely to contribute to the reduced ecdysone levels in these animals. Kni has been shown to suppress endoreplication activity in the gut by regulating cell cycle genes [48]. This is in contrast to our observation indicating that loss of kni results in a reduction in the nuclei size, and hence, reduced polyploidy of the PG cells.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that both vvl-RNAi and kni-RNAi larvae have mildly reduced PG nuclei and cell size, which is likely to contribute to the reduced ecdysone levels in these animals. Kni has been shown to suppress endoreplication activity in the gut by regulating cell cycle genes [48]. This is in contrast to our observation indicating that loss of kni results in a reduction in the nuclei size, and hence, reduced polyploidy of the PG cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Kr is required for the development of the malpighian tubules and trachea [111], larval photoreceptor organs [156], muscles [157], and extraembryonic tissue [130]. kni is involved in tracheal [158], gut [159, 160], and wing-vein development [161, 162]. hkb is required for gut development [87, 95, 102].…”
Section: Gap Genes: Phenotypes Gene Structure and Protein Productsmentioning
confidence: 99%
“…In comparison, Drosophila melanogaster KNRL and KNI are also located in tandem repeat on the third chromosome and appear to show redundancy in their embryonic responsibilities (Gonzalez-Gaitan et al, 1994; Chen et al, 1998; Fuss et al, 2001). The Daphnia KNR-R1 intron-exon boundaries show highly similar gene structure between D. magna and D. pulex .…”
Section: Resultsmentioning
confidence: 99%